2004
DOI: 10.1016/j.neuron.2004.06.001
|View full text |Cite
|
Sign up to set email alerts
|

KCNE1 Binds to the KCNQ1 Pore to Regulate Potassium Channel Activity

Abstract: Potassium channels control the resting membrane potential and excitability of biological tissues. Many voltage-gated potassium channels are controlled through interactions with accessory subunits of the KCNE family through mechanisms still not known. Gating of mammalian channel KCNQ1 is dramatically regulated by KCNE subunits. We have found that multiple segments of the channel pore structure bind to the accessory protein KCNE1. The sites that confer KCNE1 binding are necessary for the functional interaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
162
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(176 citation statements)
references
References 43 publications
13
162
0
1
Order By: Relevance
“…Binding of KCNE1 may reduce the flexibility and lower the mobility 44 , so that Phe232 may have a narrower space to avoid Phe279 during depolarization. KCNE1 is known to bind to the PD 21,22 and the voltage sensor domain 23,25 . However, the precise location of KCNE1 still remains to be elucidated 26,[44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of KCNE1 may reduce the flexibility and lower the mobility 44 , so that Phe232 may have a narrower space to avoid Phe279 during depolarization. KCNE1 is known to bind to the PD 21,22 and the voltage sensor domain 23,25 . However, the precise location of KCNE1 still remains to be elucidated 26,[44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…KCNE1 has been reported to bind to the PD of KCNQ1 21,22 , but growing evidence suggests the possibility that the VSD could be an interaction site as well [23][24][25][26] . By using the substituted cysteine accessibility method (SCAM) 27,28 , two groups including ours previously showed that KCNE1 slows the reaction rate of extracellular MTS reagents with the S4 segment, indicating that KCNE1 stabilizes the downstate of the VSD 23,29 .…”
mentioning
confidence: 99%
“…There is evidence for (13) and against (14, 15) the contribution of E1 to the pore wall and its accessibility from the pore. There is also evidence that E1 interacts with the pore domain, although not necessarily exposed in the pore (16,17), that the E1 TM helix (E1-TM) interacts directly with Q1 S4 helix (18), that E1 modulates Q1 through its C terminus (19-21), and that E1 interacts with the cytoplasmic Q1 S4-S5 linker (22).More recently, a site of possible Q1-E1 interaction was suggested by the association of mutations in Q1 S1 with congenital atrial fibrillation (8, 9). Either of these S1 mutants, S140G and V141M, when expressed heterologously, appears constitutively open, but only in the presence of E1 (8, 9).…”
mentioning
confidence: 99%
“…There is evidence for (13) and against (14,15) the contribution of E1 to the pore wall and its accessibility from the pore. There is also evidence that E1 interacts with the pore domain, although not necessarily exposed in the pore (16,17), that the E1 TM helix (E1-TM) interacts directly with Q1 S4 helix (18), that E1 modulates Q1 through its C terminus (19)(20)(21), and that E1 interacts with the cytoplasmic Q1 S4-S5 linker (22).…”
mentioning
confidence: 99%
“…Efforts to locate the KCNE1 protein in the KCNQ1 channel complex have relied on biochemical methods because no crystal structure exists for KCNQ1 in the presence or absence of KCNE1. Early work showed that KCNE1 interacts directly with the S6 pore-forming helix of KCNQ1 (11). An emergent consensus based on homology modeling and disulfide crosslinking studies suggests that KCNE1 sits between the voltage-sensing domain and pore domain of adjacent KCNQ1 subunits (Fig.…”
mentioning
confidence: 99%